The Implementation Of Management Functions In À La Carte Dinner Service at Lumbung Restaurant Seminyak - I Wayan Sonder; Ni Wayan Sumariadhi; I Wayan Wijayasa (Tourism Department, State Polytechnic of Banyuwangi, 2024)
Hotel Vila Lumbung is a four-star hotel that has a unique building architecture like a rice barn. Lumbung restaurant is a restaurant that provides a variety of a'la carte menus such as Indonesian food, western food, and Italian food, tourists can also enjoy breakfast, lunch, and dinner. This study lasted 7 months from December 1, 2023, to June 30, 2024. This study aims to determine the a la carte dinner service by waiters, the obstacles faced by waiters in serving a la carte dinner, and guest impressions of waiter service. The stages of a la carte dinner service begin with self-preparation before starting the work process, self-preparation starts from the staff arriving on time, wearing the specified uniform, taking attendance, clean the restaurant work area. Guest assessment of all elements, namely, interior (ambiance, cleanliness), service (greeting, courtesy, speed, professionalism), menu (selection/variety, presentation, taste, beverage), and others (music, lighting, entertainment), is excellent 19.11 (77%), good 4.93 (19%), sufficient 0.26 (2%). Based on the guest assessment, the a la carte dinner service at Lumbung Restaurant has been excellent where the service and problems faced in the service can be done well and satisfy guests. Meanwhile, for pricing (expensive, acceptable, good value) the price of food on the A'la carte dinner menu is considered inexpensive and appropriate by guests. This assessment is very useful for Lumbung Restaurant, because this guest comment serves as a basis for what things must be maintained, increasing guest satisfaction and correcting deficiencies.